Imaging of vertical seismic profiling data using weighted generalized radon transform migration in dip-angle domain - Li, Wuqun; Mao, Weijian; Liang, Quan (Frontiers in Earth Science, 2023)
The vertical seismic profiling (VSP) acquisition technique deploys sensors down a borehole, which often goes deep into the target area. It is easy to produce serious “smile” migration artifacts near the sensors during the migration imaging process of VSP data, which contaminates the imaging profile and affects the subsequent geological interpretation. In this paper, we analyze in detail the formation of these migration artifacts during the migration of VSP data. We extend the generalized Radon transform (GRT) migration method to the dip-angle domain and then generate dip-angle domain common image gathers (DDCIGs). Meanwhile, a variant sigmoid weighting function is applied to the DDCIGs to suppress the migration artifacts. The numerical results of synthetic and field data demonstrate high-quality DDCIG images and the significant artifact suppression capability of the proposed method.